Microbiological Test of Siomai Product - Hermanus Giman; Ni Made Ayu Suardani Singapurwa; Luh Suriati (SEAS (Sustainable Environment Agricultural Science), 2019)
This study aims to analyze the contaminants of E. coli bacteria, Salmonella sp and the Total Plate Count found in siomai food. This study uses treatment, namely siomai traders and sampling time. The data obtained were analyzed for variance and if there was a real or very real effect between the different treatments then continued with the Least Significant Difference (LSD) test of 5% and 1%. The results of this study indicate that of the 12 samples, there were 11 samples of siomai not contaminated with E. coli bacteria, and from the whole siomai samples found no contamination of Salmonella sp. Total Plate Count results on afternoon sampling at trader 6 that is 1.8 x 107 colonies / gram which is not significantly different from other treatments based on SNI 7756: 2013 concerning the quality and safety requirements of siomai namely Total Plate Count 5 x 104 colonies / gram. A total of 4.17% of the samples did not meet the standards of maximum bacterial contamination that had been determined.